The influence of information security culture towards employee’s intention to comply with information security policy: The mediation effect of attitude, normative belief and self-efficacy - Mohd Rashid, Ab Hamid; Akhyari, Nasir; Ruzaini, Abdullah Arshah; Syahrul, Fahmy; Sami, Waqas; Zuraina, Ali (Solid State Technology, 2020)
Prevalent research highlights that a positive Information Security Culture (ISC) could improve security behaviour, in particular, the employee’s intention to comply with Information Security Policy (INT) in an organization. Although there are substantial empirical studies that suggest INT is influenced by Attitude (ATT), Normative Belief (NB) and Self-Efficacy(SE), there is little evidence whether these three main constructs of the Theory of Planned Behaviour (TPB) are also present in the relationship between ISC and INT. This paper examines the mediating effects of ATT, NB and SE in the relationship between ISC and INT. A cross-sectional survey was conducted involving the respondents from Malaysian Public Universities. Partial Least Square-Structural Equation Modeling (PLSSEM) was employed to validate the research model and test the hypotheses. Findings revealed that ATT, NB and SE play significant roles as mediators in the relationship between ISC and INT. The findings further suggest that ATT, NB and SE are important in ensuring the effective establishment of ISC in improving employee’s security behaviour.